Analytical models and methodology for segregating and quantifying electric distribution system losses - Orillaza, Jordan Rel Cajudo (2003., 2003)
This research developed analytical models and methodology to segregate technical, non-technical and administrative losses of electric distribution systems. Technical losses are quantified through a three-stage approach starting from the secondary network up to the sub-transmission facilities. The non-technical loss is determined from the residual of the total system loss after accounting for the administrative and technical losses. The models and methodology were applied to two circuits of a representative distribution utility - Benguet Electric Cooperative (BENECO) where monthly and annual technical losses were analyzed. The first circuit represents a predominantly residential rural electric service while the second is an urbanized service for both commercial and residential customers. The output of this research is useful for distribution utilities for their historical and predictive performance assessment, It may also be used and administered by the utility regulator to monitor and benchmark the efficiency performance of electricity distributors. Finally, it is suitable for establishing the caps of recoverable rate of system losses.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric power systems -- Electric losses -- Philippines; Electric power distribution -- Mathematical models. -- Philippines; Electric power systems -- Management. -- Philippines; Electric power -- Load distribution; Electric power transmission -- Philippines